Pengaruh Kombinasi Akupresure dan Aromaterpi Lavender Terhadap Kualitas Tidur Wanita Menopause - Setyaningsih, Evi; Hayati, Ida; Norhapifah, Hestri (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2023)
Insomnia or difficulty sleeping will be experienced by some menopausal women. In addition, menopausal women will wake up at night and find it difficult to get back to sleep. Data from the World Health Organization (WHO) in 2018 showed that 63% of postmenopausal women complained of sleep disturbances. One effort to improve sleep quality is acupressure which can affect sleep quality. Another non-pharmacological therapy to treat insomnia is aromatherapy. Lavender aromatherapy contains antispasmodic, antiviral, and can improve sleep quality in the elderly. Purpose: To determine the effect of a combination of acupressure and lavender aromatherapy on the sleep quality of menopausal women at the Teritip Health Center in Balikpapan in 2022.